Representability of Fuzzy Biorders and Fuzzy Weak Orders - Mishra S.; Srivastava R. (My University, 2025)
In this paper, we have studied representability of both fuzzy biorders and fuzzy weak orders. It has also been shown that union of a finite family of fuzzy weak orders with respect to a t-norm T is a fuzzy quasi-transitive relation with respect to T. In the last theorem, we have obtained a characterization for a TL-representable fuzzy weak order. © 2016 World Scientific Publishing Company.